2013
DOI: 10.1371/journal.ppat.1003493
|View full text |Cite
|
Sign up to set email alerts
|

The Viral Chemokine MCK-2 of Murine Cytomegalovirus Promotes Infection as Part of a gH/gL/MCK-2 Complex

Abstract: Human cytomegalovirus (HCMV) forms two gH/gL glycoprotein complexes, gH/gL/gO and gH/gL/pUL(128,130,131A), which determine the tropism, the entry pathways and the mode of spread of the virus. For murine cytomegalovirus (MCMV), which serves as a model for HCMV, a gH/gL/gO complex functionally homologous to the HCMV gH/gL/gO complex has been described. Knock-out of MCMV gO does impair, but not abolish, virus spread indicating that also MCMV might form an alternative gH/gL complex. Here, we show that the MCMV CC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
109
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(119 citation statements)
references
References 58 publications
(101 reference statements)
4
109
2
Order By: Relevance
“…Therefore, we also tested an independently derived, K181 strain MCK2 mutant (18). Consistent with the impaired macrophage infection described for Smith strain MCK2 mutants (17), this virus infected RAW 264 monocytes significantly less well than its wild-type parent did: the level of RAW 264 cell infection as a percentage of NIH 3T3 fibroblast infection was 40.5% Ϯ 9.7% for MCMV K181 (mean Ϯ SD, n ϭ 9) and 6.4% Ϯ 1.9% for the MCK2 mutant (P Ͻ10 Ϫ7 by Student's two-tailed unpaired t test). The levels of infection of the salivary gland by the MCK2 mutant was also significantly reduced (Fig.…”
Section: Infects Both Resident Ams and Immigrant Monocytessupporting
confidence: 78%
See 1 more Smart Citation
“…Therefore, we also tested an independently derived, K181 strain MCK2 mutant (18). Consistent with the impaired macrophage infection described for Smith strain MCK2 mutants (17), this virus infected RAW 264 monocytes significantly less well than its wild-type parent did: the level of RAW 264 cell infection as a percentage of NIH 3T3 fibroblast infection was 40.5% Ϯ 9.7% for MCMV K181 (mean Ϯ SD, n ϭ 9) and 6.4% Ϯ 1.9% for the MCK2 mutant (P Ͻ10 Ϫ7 by Student's two-tailed unpaired t test). The levels of infection of the salivary gland by the MCK2 mutant was also significantly reduced (Fig.…”
Section: Infects Both Resident Ams and Immigrant Monocytessupporting
confidence: 78%
“…Infection was reduced when AMs were depleted with liposomal clodronate or when MCMV lacked m129 (15). The m131/m129 MCMV chemokine homolog (designated MCK2) attracts macrophages (16) and alters viral tropism to promote macrophage infection (17). Thus, it was concluded that AMs provide an acutely productive gateway into the lungs.…”
mentioning
confidence: 99%
“…To this end, mice were infected under otherwise identical conditions with a gO-knockout virus, mCMV-ΔgO, which lacks 532 bp at the 5′ end of the gO-encoding ORF m74 [25,31]. The deletion was introduced on the genetic background of bacterial artificial chromosome (BAC) pSM3fr-MCK-2fl, in which a preexisting frameshift mutation in m129/MCK-2 had been repaired [37] to make sure that the alternative gH/gL complex, gH/gL/MCK-2, was available for virus entry into the liver cells.…”
Section: Initiation Of the Infection In Different Hepatic Cell Types mentioning
confidence: 99%
“…In the case of murine CMV (mCMV), an alternative gH/gL complex is, instead, formed with MCK-2, the gene product of ORF m131-129 [25]. Notably, besides being part of an alternative gH/gL complex, pUL128 of hCMV and MCK-2 of mCMV share the property to act as C-C chemokines recruiting cells of the myeloid lineage [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to chemokine activity, both UL128-UL130 and their mouse counterpart, m129/m131, have been shown to also be involved in viral entry, replacing gO in the gH/gL entry complex, expanding cellular tropism to non-fibroblast cell types. (Wagner et al, 2013;Zhou et al, 2015). can activate a broad range of signalling cascades in the cell via both Gα and Gβγ subunits, which may trigger both instantaneous (e.g.…”
Section: Murid Cytomegalovirus 1 (Mcmv) Infectionmentioning
confidence: 99%